2020
DOI: 10.1017/s0033291720004924
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometer-derived sedentary time and physical activity and the incidence of depressive symptoms – The Maastricht Study

Abstract: Background This study examined the associations between accelerometer-derived sedentary time (ST), lower intensity physical activity (LPA), higher intensity physical activity (HPA) and the incidence of depressive symptoms over 4 years of follow-up. Methods We included 2082 participants from The Maastricht Study (mean ± s.d. age 60.1 ± 8.0 years; 51.2% men) without depressive symptoms at baseline. ST, LPA and HPA were measured with the ActivPAL3 activity monitor. Depressive symptoms were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(18 citation statements)
references
References 33 publications
0
18
0
Order By: Relevance
“…The differences in the findings of the present study compared with those indicating PA to be associated with better mental well-being and less mental health problems may be explained by methods used in observing PA and mental health. Devicebased measures on PA are less frequently used in mental health research (9,17,20) and findings from previous studies using device-based data have been contradictory. The meta-analysis by Gianfredi et al (10) showed a potential protective effect of PA on prevalent and incident of depression, similar to the findings of the study by Choi et al (11).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The differences in the findings of the present study compared with those indicating PA to be associated with better mental well-being and less mental health problems may be explained by methods used in observing PA and mental health. Devicebased measures on PA are less frequently used in mental health research (9,17,20) and findings from previous studies using device-based data have been contradictory. The meta-analysis by Gianfredi et al (10) showed a potential protective effect of PA on prevalent and incident of depression, similar to the findings of the study by Choi et al (11).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence on the role of accelerometer-based PA in mental health outcomes exist also in studies using samples of children and adolescents (25). However, Konopka et al (20) found no association between accelerometer-based SB or PA with depression symptoms in men. Similarly, a cohort study by Bell et al (34) found no evidence of an association between accelerometer-based PA, mental well-being and symptoms of mental disorders, but the sample consisted of adolescents and the findings are therefore not comparable with the findings of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations